The Optimization of Efficiency in Grid-Connected PV Systems in Tropical Climates Using a Single-Axis Solar Tracker Based on Simulation - Hendra Budiono Putra Parapa; Rachmawan Budiarto; Mohammad Kholid Ridwan (International Journal Labs, 2026)
The high potential for solar radiation in the tropics demands a Solar Power Plant (PLTS) system that can adapt to the sun's dynamic annual movements. Conventional fixed-tilt systems tend to be suboptimal at low latitudes due to the limited variation in solar radiation angle throughout the year. This study aims to evaluate and optimize the performance of on-grid solar power plants using a horizontal east-west single-axis solar tracker (SAT), as well as to analyze the effect of increased thermal losses on system efficiency in tropical climatic conditions. The case study was conducted on an on-grid solar power plant with a capacity of 50.4 kWp located in Mawang, Makassar (5.22° S), with a fixed-tilt system at a tilt angle of 17° as a comparison. The research methodology used a PVsyst software-based simulation approach with the activation of a backtracking scheme to mitigate inter-row shading at a ground coverage ratio of approximately 55.8%. The simulation results showed that the application of single-axis trackers increased the annual energy channeled to the grid (EGrid) by 4.81%, equivalent to 3,149 kWh. However, the increase in the Performance Ratio (PR) was relatively limited, from 0.794 to 0.798, due to the increase in module thermal losses reaching 13.3%. These findings make a quantitative contribution regarding the trade-off between increased irradiation capture and thermal penalty in the application of single-axis trackers in the tropics, and confirm that the optimization of tracking systems depends not only on optical aspects but also on the thermal management of photovoltaic modules.